Small herbivores with big impacts: Tundra voles (Microtus oeconomus) alter post‐fire ecosystem dynamics. Issue 7 (25th May 2022) - Steketee, Jess K.; Rocha, Adrian V.; Gough, Laura; Griffin, Kevin L.; Klupar, Ian; An, Ruby; Williamson, Nicole; Rowe, Rebecca J.
Abstract: Fire is an important ecological disturbance that can reset ecosystems and initiate changes in plant community composition, ecosystem biogeochemistry, and primary productivity. As herbivores rely on primary producers for food, changes in vegetation may alter plant–herbivore interactions with important—but often unexplored—feedbacks to ecosystems. Here we examined the impact of post‐fire changes in plant community composition and structure on habitat suitability and rodent herbivore activity in response to a large, severe, and unprecedented fire in northern Alaskan tundra. In moist acidic tundra where the fire occurred, tundra voles ( Microtus oeconomus ) are the dominant herbivore and rely on the tussock forming sedge Eriophorum vaginatum for both food and nesting material. Tundra voles were 10 times more abundant at the burned site compared with nearby unburned tundra 7‐12 years after the fire. Fire increased the habitat suitability for voles by increasing plant productivity and biomass, food quality, and cover through both taller vegetation and increased microtopography. As a result of elevated vole abundance, Eriophorum mortality caused by vole herbivory was two orders of magnitude higher than natural mortality and approached the magnitude of the mortality rate resulting directly from the fire. These findings suggest that post‐fire increases in herbivore pressure on Eriophorum could, in turn, disrupt graminoid recovery and enhance shrub encroachment. Tundra state transitions from graminoid to shrub dominated are also evident following other disturbances and fertilization experiments, suggesting that as Arctic temperatures rise, greater available nutrients and increased frequencies of large‐scale disturbances may also alter plant–animal interactions with cascading impacts on plant communities and ecosystem function.